Collagen XXVII organises the pericellular matrix in the growth plate. - Darren A Plumb; Laila Ferrara; Tanja Torbica; Lynnette Knowles; Aleksandr Mironov; Karl E Kadler; Michael D Briggs; Raymond P Boot-Handford (PLoS ONE)
In order to characterise the function of the novel fibrillar type XXVII collagen, a series of mice expressing mutant forms of the collagen were investigated. Mice harboring a glycine to cysteine substitution in the collagenous domain were phenotypically normal when heterozygote and displayed a mild disruption of growth plate architecture in the homozygous state. Mice expressing an 87 amino acid deletion in the collagenous domain of collagen XXVII were phenotypically normal as heterozygotes whereas homozygotes exhibited a severe chondrodysplasia and died perinatally from a lung defect. Animals expressing the 87 amino acid deletion targeted specifically to cartilage were viable but severely dwarfed. The pericellular matrix of proliferative chondrocytes was disrupted and the proliferative cells exhibited a decreased tendency to flatten and form vertical columns. Collagen XXVII plays an important structural role in the pericellular extracellular matrix of the growth plate and is required for the organisation of the proliferative zone.